Thermal Performance Evaluation of a Channel Installed with Inclined-Baffle Turbulators - Phila, A.; Eiamsa-ard, S.; Thianpong, C. (My University, 2020)
This study shed light on how heat transfer in a rectangular channel can be significantly enhanced by integrating it with inclined baffles. Experiments were performed to investigate the effect of the inclined baffles at different attack angles (θ) of 0° up to 165° in 15° incremental steps. The pitch length (between the consecutive baffles) to baffle height ratio (P/e) and the baffle height to channel height ratio (e/H) remained constant at 10 and 0.15, respectively. Experiments on a channel without baffles and one with typical transverse baffles (θ = 90°) were also conducted for comparison. Temperatures measured by the thermochromic liquid crystal image processing technique were employed for plotting the temperature contours on the heated surface. The Reynolds number associated with turbulent flow varied from 9000 to 24,000 under a constant wall heat flux scenario. The heat transfer and pressure drop were characterized by the Nusselt number (Nu) and friction factor (f), respectively. The results showed a promising ability of the inclined baffles to improve the heat transfer rate in the channel, however, this came at the price of an increased pressure drop in the system. The impact of the attack angle on heat transfer and thermal efficiency showed that a 60° attack angle was superior to other attack angles. The results were comparable to those for a 120° attack angle. Additionally, this attack angle enabled the system to accomplish a zenith thermal enhancement factor (η) of 1.11 at a Reynolds number of 9000.
Keywords: Heat exchanger; Heat transfer enhancement; Inclined baffle; Rectangular channel